EKONOMI ISLAM, INDEKS KEBAHAGIAAN MAQASHID SYARIAH DAN INDEKS KOTA ISLAM - Dwi Joko Siswanto; Ickhsanto Wahyudi; Tantri Yanuar Rahmat Syah (JURNAL CAFETARIA, 2023)
This study looks for relevance between Islamic economics, maqashid sharia, happiness index, and Islamic index. The writing method uses discourse analysis as a reading tool to interpret the discourse discussed. The results of this study indicate that the goal of the economy is well-being, which is not only based on material values. have similarities between the Islamic index, happiness and maqashid sharia. Likewise, there is a crucial aspect of the monotheistic view which is inherent in Islam which is not reflected in the happiness and islamicity index. This approach can therefore serve as a productive dialogue to address the common challenges posed by the global market economy and propose more ethical forms of market organizations and institutions, such as employee-owned enterprises and cooperatives. This dialogue can encourage the revival of the non-profit sector and encourage critical introspection of the economy, the Islamic banking and finance industry. Finally, collaborative efforts are needed to transform this model into an Islamic welfare index as a tool for policy makers and as a goal of national and regional cooperation, particularly between Islamic countries.